1997
DOI: 10.1080/00223989709603503
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Sacred and Secular Music on Elderly People

Abstract: Two kinds of music, sacred and secular, were played to elderly participants and rated by them on various aspects of evoked feelings. Additionally, pre- and posttest batteries of questionnaires were administered to measure the spirituality and ego integrity of the listeners. Statistical analyses of the findings failed to reveal significant effects on the spirituality of the participants, although the two kinds of music were rated differently. When results for all the music were combined, a significant and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 8 publications
1
23
0
1
Order By: Relevance
“…It is, however, somewhat higher than the 124.00 for the 50% quantile reported by Salamon and Conte (1984) from their norm sample of participants aged 80 and over, suggesting that the present sample represented a more satisfied cohort. The mean INSPIRIT score at 19.80 is very close to the 19.60 reported by Kass et al (1991) from their reliability sample aged 25 to 72, but slightly lower than the 22.17 obtained by Lowis and Hughes (1997) in their study of retired men and women.…”
Section: Descriptive Statisticssupporting
confidence: 53%
See 1 more Smart Citation
“…It is, however, somewhat higher than the 124.00 for the 50% quantile reported by Salamon and Conte (1984) from their norm sample of participants aged 80 and over, suggesting that the present sample represented a more satisfied cohort. The mean INSPIRIT score at 19.80 is very close to the 19.60 reported by Kass et al (1991) from their reliability sample aged 25 to 72, but slightly lower than the 22.17 obtained by Lowis and Hughes (1997) in their study of retired men and women.…”
Section: Descriptive Statisticssupporting
confidence: 53%
“…= 11.2) (Kass et al, 1991); it is not known if any assistance was given during administration to the older participants. No help was necessary when the LSES was previously administered by Lowis and Raubenheimer (1997), and the INSPIRIT by Lowis and Hughes (1997). The maximum ages of participants in these cases were 84 (M = 69.8) and 90 (M = 76.7) respectively, and all individuals were still living independently.…”
Section: Discussionmentioning
confidence: 99%
“…Since that date a considerable body of research has explored the therapeutic use of music for a wide range of physical, neurophysiological and psychosocial problems, as well as the supplementary role of music to alleviate pain and reduce stress and anxiety, in the contexts of medical and surgical procedures (Maranto, 1991). Empirical studies have also investigated the impact of music among healthy individuals on self-reported mood and emotional experience (Hargreaves and North, 1999;Lowis, 1998;Lowis and Hughes, 1997;McCraty et al, 1996;Panksepp, 1995), on measures of cognitive performance and learning (Savan, 1999;Waleson, 2000), and on objective indicators of physiological, neurological and immuno-logical function (Charnetski et al, 1998;Krumhansl, 1997;McCraty et al, 1996). A striking feature of much of the experimental literature in this field, however, is the focus on passive exposure to brief extracts of music in relatively artificial conditions.…”
Section: Music and Healthmentioning
confidence: 99%
“…Ethnomusic therapy and an avoidance of music incongruency are described by Campinha‐Bacote & Allbright (1992) as important considerations in the treatment of particular patient groups such as African Americans. Folta (1993) stated that gospel songs and hymns and songs of praise could be used to supplement spiritual care and Lowis & Hughes (1997) concluded, from the results of a small experiment, that sacred and secular music could be used as valuable adjuncts to relaxation and life review. Gitanjali (1998), in a study performed in India with a very small sample of eight, found no evidence to support the idea that listening to a traditional Neelambari raga could induce sleep.…”
Section: The Literature Reviewmentioning
confidence: 99%